Implementation of School-Based Management (SBM) in Im-proving Teacher Performance and Learning Quality in Public Elementary Schools (International Journal of Education and Literature, 2025)
This study is motivated by the importance of implementing School-Based Management (SBM) as a decentralization strategy in education to enhance management effectiveness and improve the quality of learning in public elementary schools. Many schools still face challenges such as low teacher performance, limited community participation, and weak transparency and accountability in educational management. The purpose of this study is to analyze the implementation of SBM principles in improving teacher performance and the quality of learning at the elementary school level. The research method employed is qualitative with a descriptive approach, based on a literature review drawn from various scholarly journals, books, and official documents relevant to SBM, teacher performance, and learning quality. The results show that SBM plays a crucial role in strengthening school autonomy, increasing stakeholder participation, and fostering transparent and accountable management systems. Through democratic school leadership and a collaborative work culture, SBM enhances teacher professionalism and encourages innovation in the learning process. Therefore, SBM proves to be an effective approach to achieving sustainable improvement in the quality of elementary education.